Racial and Gender Identity Among Black Adolescent Males: An Intersectionality Perspective. Issue 2 (3rd November 2014) - Rogers, Leoandra Onnie; Scott, Marc A.; Way, Niobe
Abstract : A considerable amount of social identity research has focused on race and racial identity, while gender identity, particularly among Black adolescents, remains underexamined. The current study used survey data from 183 Black adolescent males (13–16 years old) to investigate the development and relation between racial and gender identity centrality and private regard, and how these identities impact adjustment over time. It was found that dimensions of racial and gender identity were strongly correlated. Levels of racial centrality increased over time while gender centrality, and racial and gender private regard declined. In addition, racial and gender identity uniquely contributed to higher levels of psychological well‐being and academic adjustment. These findings are discussed within the context of existing identity theories and intersectionality theory.